Optimalisasi Peran Pemuda Dalam Pengelolaan Sampah Melalui Program Bank Sampah Di Dusun Babat Desa Randupitu - Muchammad lubbil khobir lubbil; Solchan Ghozali (Universitas Darunnajah, Jakarta, Indonesia, 2024)
Optimizing the role of youth through community empowerment in waste management has proven to be an effective method in addressing environmental issues while increasing community awareness and economic growth. This study evaluates the implementation of the Bank Sampah initiative in Babat Hamlet, Randupitu Willage, focusing on ease of use as a means to encourage community participation and environmental education. Data wasobtained through observation, group discussions, and in-dhept interviews. The results showed that the use of this tool can motivate the community to actively participate in waste conservation and also generate economic benefits through the utilization of waste as an energy source. This research contributes to inclusive community development by empowering the younger generation as the main contributors.